A novel coumarin, (+)-3′-angeloxyloxy-4′-keto-3′, 4′-dihydroseselin, isolated from Bupleurummalconense (Chaihu) inhibited NF-κB activity. Issue 1 (December 2016) - Mu, Huai-Xue; Lin, Cheng-Yuan; Huang, Lin-Fang; Yang, Da-Jian; Lu, Ai-Ping; Han, Quan-Bin; Bian, Zhao-Xiang
Abstract Background This study aims to identify the major anti-inflammatory components in the petroleum ether extract ofBupleurum malconense (Chaihu ), by bioassay-guided fractionation, and to investigate the anti-inflammatory mechanisms of active components in lipopolysaccharide (LPS)-stimulated murine macrophage RAW-Blue cells. Methods A QUANTI-Blue assay was used to guide fractionation ofB. malconense root extract. The petroleum ether extract which exerted significant secreted embryonic alkaline phosphatase (SEAP) inhibition effect was purified by silica gel column chromatography and assisted with reverse phase HPLC. The major bioactive compound which significantly inhibited SEAP activity was obtained and its anti-inflammatory effects in LPS-induced RAW-Blue cells were measured by the overproduction of NO (Griess method), gene expression ofIl -1β, Tnf -α andiNos (real-time PCR). In parallel, protein expressions of COX-2, iNOS and IκB-α were determined by western blot. Results In bioassay-guided fractionation using LPS-stimulated mouse macrophage RAW-Blue cells, (+)-3′-angeloxyloxy-4′-keto-3′, 4′-dihydroseselin (Pd-Ib) was identified by MS and NMR spectral analyses. Pd-Ib (5, 10, 20 μg/mL) suppressed the gene expression ofIl -1β (P < 0.0001, P < 0.0001, P < 0.0001 for three respective concentrations), Tnf -α (P = 0.006, P = 0.001, P < 0.0001 for three respective concentrations) andiNos (P = 0.009, P < 0.0001, P < 0.0001 for three respective concentrations) in LPS-stimulated macrophages. The production of cyclooxygenase-2 (P = 0.019, P = 0.002, P < 0.0001), iNOS (P < 0.0001, P < 0.0001, P < 0.0001 for three respective concentrations) and NO (P < 0.0001, P < 0.0001, P < 0.0001 for three respective concentrations) significantly decreased when macrophages were treated with Pd-Ib (5, 10, 20 μg/mL) in the presence of LPS. Pd-Ib (5, 10, 20 μg/mL) suppressed the nuclear activation of NF-κB while it up-regulated the IκB-α level (P = 0.028, P = 0.013, P = 0.005 for three respective concentrations) in LPS-stimulated macrophages. Conclusions Pd-Ib isolated fromB. malconense suppressed LPS-induced inflammatory responses in macrophages by inhibiting NF-κB activity and reducing the expression of iNOS, COX-2 as well as pro-inflammatory cytokines.